(untitled) (Journal of Economic Research & Business Administration, 2015)
In Kazakhstan the system of business support has been This question is worked through on the state level by the Ministry of Industry and Trade, the Ministry of Economics and Budget Planning, the Ministry of Finance, Agency of Natural Monopolies, Statistics Agency and other executive authorities. To support small business some state and local funds have been created. Nevertheless in Kazakhstan to support small business this field is not developed evenly. According to the world experience, its development is connected with state support, with requirements of this activity from businessmen, persons interested in development of individual business. In strategy Kazakhstan-2050” .all-round business support.s as leading power of national economics is of great value. In addition the obstacles from administration will decrease, mechanisms of strict measures of state activity on man-made obstacles in development of enterprises will be taken. In connection with such support by 2030 a part of small and medium business in economics should be increase at least twice. Economic modernisation started with independence requires solving a lot of problems. Numerous programs have been accepted. Some kinds of plans and projects have been realized. Therefore economic breakthrough has increased, power has appeared.